3D seismic discontinuity attributes analyses for low – permeability reservoir sand fractures characterisation: an onshore example from Niger delta, Nigeria. Issue 1 (1st January 2021) - Amigun, J. O.; Akinleye-Martins, O. A.
ABSTRACT: In hydrocarbon exploration, fractures act as possible pathways for hydrocarbon flow especially in low-permeable siliciclastic reservoirs and carbonate reservoir layers. These fractures on typical seismic section are designatesub-seismic scale structures, occur below seismic resolution and thus difficult to detect on seismic section. This study aims to predict and characterise sub-seismic scale fractures within low-permeability siliciclastic reservoirs of Agbada Formation in "Kin" Field onshore Niger Delta basin by using discontinuity attributes i.e. similarity and curvature. The input seismic data of the study field was initially conditioned using the dip steering algorithm to improve the image quality of fractures in the data. Time-slices were extracted within the horizons of interest for seismic attribute analysis. Conventional log from porosity density was used to validate the interpreted fractures within the borehole environment. The attribute analyses result at time-slices 2024 ms, 2100 ms and 2197 ms show subtle features i.e. fractures with predominant trends NW – SE and NE – SW. A multi-attribute analysis was performed to optimise fractures prediction. Further results show relatively high fracture density at the western central and south eastern regions of the study area. Therefore, these regions could be inferred as potential hydrocarbon zones and locations for future wells placement.